One Pot Spiropyrazoline Synthesis via Intramolecular Cyclization/Methylation - Dadiboyena, Sureshbabu (2011)
Regioisomeric spiropyrazolines were synthesized through a tandem intramolecular cyclization/methylation reaction of a functionalized 5,5-disubstituted pyrazoline in one reaction vessel. The 5,5-pyrazolines were constructed through a 1,3-dipolar cycloaddition reaction of aromatic ring containing nitrile imines and a disubstituted geminal alkene. An evaluation of the relative location of the nucleophilic and electrophilic functional groups on the pyrazoline was performed in order to ascertain the best pyrazoline system for the intramolecular cyclization/methylation reaction. Higher spiropyrazoline isolated yields were realized from pyrazolines with the electrophilic ester located further away from the pyrazoline when compared to pyrazolines with a directly bonded ester.